STATE OF VASCULAR-THROMBOCYTARY HEMOSTASIS IN CHRONIC LIVER DISEASES OF VIRUS ETIOLOGY - Nuriddinova Nodira Faxriddinovna., Kurbonova Zumrad Chutbaevna (Journals Park Publishing, 2023)
The review of the literature provides information on changes in vascular-platelet hemostasis, platelet count, disorders of adhesion and aggregation properties, hemorrhagic complications in chronic liver disease. The results of the study of vascular-platelet hemostasis in patients with chronic liver diffuse disease were analyzed.
Keywords: Hepatotropic viruses, hepatitis, liver cirrhosis, platelets, adhesions, aggregation.